Citizen Participation in the Implementation of Educational Policies in Colombia - Arias Calderón, Enrique; Ceballos Molano, Raquel; Otálvaro Marín, Bairon; Martínez Sander, Ángela M.; Córdoba Hoyos, Lyda T. (Cuadernos de Administración, 2015)
This analysis responds to a qualitative study on the effectiveness of the judicial principle of citizen participation in the implementation of educational public policies in Colombia at the basic level. Qualitative research methodology was used and the results permit contrasting the main bibliographic and documentary findings, from a social-judicial approach, which seeks to recognize the effectiveness of the precept of participation by the so-called recipients of the judicial norm consecrated in the Political Constitution as in the legislation. The reflection proposed was made from the perspective associated to reform processes of the State in Latin America during the mid 1990s, which sought to implement strategies to democratize and generate trust in public management. This theoretical analysis permitted evidencing the principal challenges confronted by citizen participation against institutional practices, above all local, in charge of the implementation of public policies on the quality of education at the basic level